CONSTRUCTIVIST EPISTEMOLOGY IN SCIENCE LEARNING FOR ḤALĀLAN-ṬAYYIBAN FOOD SUBJECT - Iis Sumiati; Irawan Irawan; Aan Hasanah (Sekolah Tinggi Agama Islam Sadra, 2024)
In the era of globalization, a deep understanding of the ḥalālan ṭayyiban food concept is becoming increasingly important. How we, especially the nation’s young generation, must understand, internalize, and apply these principles in our daily lives is an increasingly urgent challenge. Learning the concepts of ḥalāl food and thayyib is no longer just a matter of factual knowledge, but is also a deep ethical and religious responsibility. This article aims to prove and evaluate a relevant and innovative learning approach to be applied in schools in re-conceptualizing the subject of ḥalālan ṭayyiban food in science subjects. The method used in the research was the pre-experiment method with a sample of 37 students in grades 4, 5, and 6 at The Mother Foundation Elementary School, who were selected randomly. Data collection was carried out using a quantitative and qualitative approach (mixed method) which was then analyzed descriptively using an epistemological philosophy of science perspective. Data obtained was taken using interview instruments and concept understanding tests. The results of this research show that the constructivist epistemological approach can increase students' conceptual understanding of the subject of ḥalālan ṭayyiban food with the gain calculation being in the high category. This proves that the constructivist epistemological approach can provide meaningful learning that directs students to explore their thinking in more depth.